WAYS OF FUTURE MUSIC TEACHERS’ COMMUNICATIVE COMPETENCE FORMING - ZHANG, Gege (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2024)
Annotation. Analysis of the scientific literature was fulfilled, which indicated the importance of the communicative competence acquisition by future music teachers since a high level of communication skills positively contributes to the professional and educational mobility of students, the successful adaptation of the individual to the changing conditions of the pedagogical reality, professional self-development and self-realization of the teacher throughout the entire conscious-professional life. The impact of dynamic changes on the development of music education, which includes various musical styles, techniques and teaching methods, is noted. The essential role of students' participation in simulated educational situations, role-playing games, and master classes under the guidance of a teacher, which serves to improve communication skills and understanding of all aspects of communication by musical art students, is noted. Attention is focused on the need for education seekers to use modern information and communication technologies and information resources for mixed forms of education, as the use of online platforms in education will facilitate the communication of future teachers without time and geographical limitations with the help of video conferences, online courses and interactive seminars. Compensation for the development of personal interaction in distance or mixed forms of education is possible with the introduction of a comprehensive model of education that combines virtual reality (VR) and augmented reality (AR) technologies to practice teaching and communication skills using online simulation of learning and interaction in a virtual environment. It has been established that future music teachers should not only impart musical knowledge but also communicate effectively with students, parents, and colleagues during the educational process. To solve these problems, students need systematic training in communication skills. The main ways of forming communicative competencies in the professional activities of future music teachers have been studied, in particular, the participation of students in training and seminars, interdisciplinary cooperation, and family and community involvement in musical and artistic activities.